EXPLORING TEACHERS’ CHALLENGES IN TEACHING ENGLISH TO YOUNG LEARNERS AT SD KATOLIK SANTA THERESIA - Sartika Bobrikit; Naniek Jusnita; Silvani Umar Ali; Suratman Dahlan (FKIP Universitas Khairun, 2020)
The objective of this research is to know teachers’ challenges in teaching English to young learners. This is a qualitative research that used qualitative method with interview as research instrument. The researchers selected two English teachers at SD Katolik Santa Theresya. The results show that there were some challenges that faced by the teachers in teaching English to young learners such as teaching listening, motivating students to learn English, and lack of textbook to faciltate the students’ needs. In teaching listening; the teachers found the challenges such as the students were difficult to comprehend or understand when the teachers spoke quickly. The teachers had some strategies to solve the problems to motivate the students, gave attention and care with the students. Besides, using of text book is not related with the students’ need becomes the challenges in teaching English. To solve it; the teachers make another alternative book such as LKS to support the teachers in teaching English in the classroom.